BEYOND ELT CHALLENGES AND PRACTICES IN THAILAND - Ummi Rasyidah (Premise: Journal of English Education and Applied Linguistics, 2017)
This paper attempts to provide insight views in English Language Teaching practices in Thailand. Given the understanding of educational system, later it is engaging a brief overview of challenge in English Language Teaching. This paper is to explore teachers’ understanding of the students-centered approach and their actual classroom practices in Thai schools. It is also grounded concepts and practices of ICT. This paper may adopt some practices or features in Thailand context that might be implemented in Indonesia where these two countries; Indonesian and Thailand share similarity in educational system.